2013
DOI: 10.1590/s1517-83822013000300049
|View full text |Cite
|
Sign up to set email alerts
|

Mycological contamination in dental unit waterlines in Istanbul, Turkey

Abstract: Studies on dental units (DUs) are conducted either for the prevention or the reduction of the density of bacterial contamination in dental unit waterlines (DUWLs). However, the existence of fungi in the these systems requires more attention. During dental treatment, direct contact with water contaminated with fungi such as Candida, Aspergillus, or inhalation of aerosols from high-speed drill may cause various respiratory infections, such as asthma, allergies, and wounds on mucose membranes, especially on immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 36 publications
3
21
0
5
Order By: Relevance
“…in water of dental units was reported by several authors. The results of predominant isolated strains from DCUWLs obtained from this study corroborated those of Szymańska and Kadaifciler et al ,. which demonstrated that the most isolated yeasts were C. albicans , C. guilliermondii , C. famata , C. curvata and Geotrichum candidum .…”
Section: Discussionsupporting
confidence: 91%
“…in water of dental units was reported by several authors. The results of predominant isolated strains from DCUWLs obtained from this study corroborated those of Szymańska and Kadaifciler et al ,. which demonstrated that the most isolated yeasts were C. albicans , C. guilliermondii , C. famata , C. curvata and Geotrichum candidum .…”
Section: Discussionsupporting
confidence: 91%
“…4,5 Although yeast species were less commonly found in the present investigation, their diversity is corroborated by data from other studies, involving water from different sources. 14 open wounds. 14,15 Similarly, Aureobasidium pullulans, which was detected in water from both types of wells ( Table 1), poses a risk to the health of immunosuppressed consumers, because this species can survival in water distribution systems.…”
Section: Discussionmentioning
confidence: 99%
“…Moraxella osloensis, on the other hand, is known to be a major causative bacterium of respiratory tract infection, and has been reported to show penicillin resistance [12]. Previous studies have also suggested that dental employees should consider the risk of infection as they are frequently exposed to bioaerosols [13,14]. For the prevention of infectious diseases, it is efficient to prevent exposure to infection or to prevent contamination by an infection medium, and direct contact with bacteria should be avoided.…”
Section: Discussionmentioning
confidence: 99%